Evaluation of umbilical cord pulsatility after vaginal delivery in singleton pregnancies at term. (May 2019) - Di Tommaso, Mariarosaria; Carotenuto, Bianca; Seravalli, Viola; Magro Malosso, Elena R.; Pinzauti, Serena; Torricelli, Michela; Petraglia, Felice
Abstract: Objectives: To define the duration of umbilical cord pulsatility (UCP) after vaginal delivery and to evaluate its possible association with maternal characteristics and obstetric and neonatal variables. Study design: Prospective observational study on women with a singleton pregnancy at term who had a vaginal delivery and cord clamping at the cessation of pulsations. The collection of UCP duration was performed through a stopwatch and by manual palpation of the umbilical cord. Maternal (age, BMI, parity, antepartum hemoglobin), obstetric (pregnancy characteristics, gestational age at delivery, induction of labor, duration of the first, the second and the third stage of labor, post-partum blood loss, umbilical cord length) and neonatal (birthweight, Apgar score, hematocrit, hemoglobin) variables were then compared between two groups: long-term vs. short-term UCP. Results: A total of 102 women were identified. The median duration of UCP after birth was 213 s (IQR 120, 420), corresponding to 3 min and 33 s. The long-term UCP group (n = 51) had a significantly longer duration of third stage of labor (median 12 vs. 8 min, p < 0.001) and a significantly higher birthweight (median 3530 g vs. 3250 g, p = 0.005) compared with the short-term UCP group (n = 51). No differences in the other variables were found between groups. Conclusion: For the first time we have reported the duration of UCP after vaginal delivery. An increased duration of UCP is associated with a prolonged duration of third stage of labor and a higher birthweight.